Freemasons (Williamsburg, Va.) records - Freemasons (Williamsburg, Va.)
Photocopies of pages from minutebooks of the masonic lodge at Williamsburg, Va.
Negative photostats.
Collection material in English.
Keywords: Freemasonry -- Virginia -- Williamsburg